2022
DOI: 10.3389/fcell.2022.852878
|View full text |Cite
|
Sign up to set email alerts
|

Integrin Regulated Autoimmune Disorders: Understanding the Role of Mechanical Force in Autoimmunity

Abstract: The pathophysiology of autoimmune disorders is multifactorial, where immune cell migration, adhesion, and lymphocyte activation play crucial roles in its progression. These immune processes are majorly regulated by adhesion molecules at cell–extracellular matrix (ECM) and cell–cell junctions. Integrin, a transmembrane focal adhesion protein, plays an indispensable role in these immune cell mechanisms. Notably, integrin is regulated by mechanical force and exhibit bidirectional force transmission from both the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 330 publications
0
3
0
Order By: Relevance
“…The key role of integrins in triggering immune mechanisms has been largely described, even if their involvement in the onset and progression of autoimmune diseases (including CD) remains elusive. 40 This set of miRNAs could have potential future applications in clinical trials for the diagnosis and monitoring of CD as well as therapeutic targets to reduce villous atrophy.…”
Section: Discussionmentioning
confidence: 99%
“…The key role of integrins in triggering immune mechanisms has been largely described, even if their involvement in the onset and progression of autoimmune diseases (including CD) remains elusive. 40 This set of miRNAs could have potential future applications in clinical trials for the diagnosis and monitoring of CD as well as therapeutic targets to reduce villous atrophy.…”
Section: Discussionmentioning
confidence: 99%
“…ITGAL is the integrin alpha L chain, and integrin is associated with autoimmunity [ 41 ]. Both ITGAL and ITGA4 (integrin subunit alpha 4) were identified as two of the 12 candidate genes in the current study and may be associated with the pathophysiology of PBC.…”
Section: Resultsmentioning
confidence: 99%
“…Changes in mechanical properties, the increase in ECM, and tissue stiffness contribute to disease development and progression [ 195 , 196 , 197 , 198 ]. Notably, many studies have demonstrated that tissue stiffening enhances integrin signaling [ 199 , 200 ], and increasing evidence on enhanced ECM stiffness-induced cellular senescence has provided important insights into the pathogenesis of age-related diseases, including OA, abdominal aortic aneurysm, and IDD [ 34 , 201 , 202 , 203 , 204 , 205 ]. Wang and colleagues recently found that the increased stiffness of human NP tissue specimens with IDD is correlated with an increase in the degeneration grade [ 203 ].…”
Section: Potential Strategies Targeting Cellular Senescence By Blocki...mentioning
confidence: 99%